EFFECT OF HEAT STRESS ON PRODUCTION PERFORMANCE IN DAIRY ANIMALS - ULLAH, M; IBRAHIM, M; HUSSAIN, T; ULLAH, A; HUSSAIN, A; SAHIN, T; AHMED, S; KHAN, AMA; SADIQ, AB; SHAH, KA (Biological and Clinical Sciences Research Journal, 2024)
The high-temperature stress and combination of high temperature and humidity during summer months in Punjab is an important factor for dairy cows as it directly affects the daily milk yield of dairy cows. The research was conducted on to effect of high-temperature stress on different parameters associated with daily milk yield. For this purpose, 5 freshly parturated Sahiwal breeds of dairy cows were to evaluate the effect of temperature humidity index on Daily milk yield at different temperature humidity index levels i.e. comfortable (≤ 70), mild stress (71–80), moderate stress (81–90), and stressful (≥90) zone. Blood samples were collected and centrifuged to get serum and ELISA was accomplished by using a spectrometer. Results revealed high significant (P < 0.001) increment in cortisol and triglycerides concentration and high significant reduction in serum progesterone (P < 0.001) and Luteinizing hormone (P < 0.001) concentration in cows during stressful environments. Daily milk yield has significant (P < 0.05) variation and a decreasing trend in cows from comfortable to stressful conditions. Progesterone and LH had a highly significant positive correlation with daily milk yield. Cortisol and triglycerides had a non-significant negative correlation with daily milk yield. It is concluded that heat stress has a negative impact on the daily milk yield as it disturbs the hormonal balance of the animal.